Linguistic werk in streamed drag: A translational and translanguaging analysis - Iván Villanueva-Jordán (Translation and Interpreting : the International Journal of Translation and Interpreting Research)
In this article, I analyze the inter-and intralingualrelationships of twointernational editionsof the Drag Race franchise, Drag Race Españaand Drag Race México. This study aims to discover how drag is indexicalized through translation and translanguaging strategies and how these strategies reconfigure the representation of local drag culture, subjectivities, and communities in relationship to globally owned formatsdistributed through streaming. The study follows a qualitative approach. Six episodes of each show were selected following non-probabilistic or purposive criteria. These criteria included (a) having episodes with different structures and (b) gathering dialogues from varied situations and most drag contestants. All the dialogues from the selected episodes were analyzed using a comparative approach. The rationale for this methodology is that contrasting mediatized transnational gendered representations can lead to a better understanding of how symbolic and cultural capital isinserted in television formats to favor their consumption through different distribution technologies, translation, and translanguaging strategies.